In Pulmonary Tuberculosis Direct Smear Sputum is a Prognostic Factor for Cure - Leon-Abarca, Juan Alonso (2019)
Background: According to the World Health Organization, tuberculosis produces around 1.5 million deaths worldwide each year. In Peru, during the 2011-2015 period, incidence and morbidity rates have decreased from 97.4 to 87.4 and from 109.7 to 99.5 respectively. However, tuberculosis remains as the fifteenth cause of death. The clinical evolution of these patients will depend on many factors, such as adherence to treatment, comorbidities, drug resistance of the pathogen. Therefore, it is the presence and interaction of these factors that help us predict which patients could potentially fail during the treatment. Objective: To determine in patients with pulmonary tuberculosis whether direct smear study at the beginning of treatment is a prognostic factor of the discharge condition. Methods: We performed a secondary analysis of the database of the retrospective cohort study "Evaluation of the treatment of the Tuberculosis Control Program (PCTBC) in a hospital of III level in Lima - Peru from 1972 to 2012". The study population was 1635 patients. At the beginning of the treatment, 24.16% had a negative sputum smear, while 75.84% had a positive smear. Within these patients, 50.96% had 1+, 27.17% had 2+, and the remaining 21.85% had 3+. Results: Patients with negative direct smear had higher cure rates (95.19% vs 90.24%, p = 0.0029). Among those with positive smear, cure rates were similar between those with 1+ and 2+, but was higher in the 1+ group when compared to 3+ patients (95.19% vs 90.24%, p = 0.0057) and 2+ compared to those with 3+ (95.19% vs 90.24%, p = 0.0062). Conclusion: In a PCTBC of a tertiary hospital, patient’s evolution are related to the bacillar charge at the beginning of the treatment. Cure rates are higher in those with less bacillar charge while death and failure are higher in those with higher bacillar charge.